2018
DOI: 10.4236/psych.2018.97098
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence for a New Class of Personality Disorder: The Safety-Oriented Personality Style or Phobicentric Psychopathology (SOPS/PCP) and Impact on Personality Psychology

Abstract: This study is aimed at establishing that the Safety-Oriented Personality Style (SOPS) or Phobicentric Psychopathology (PCP) is an actual mental disorder representing a disproportionate, self-focused pattern of reacting to ordinary fear-anxiety situations. SOPS/PCP is most similar to Neuroticism in the widely accepted Big 5 model. The presentation of personality within a dimensional structure is in contradistinction to that of the lately criticized category-based Diagnostic and Statistical Manual (DSM). Nonethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 123 publications
(121 reference statements)
1
26
0
Order By: Relevance
“…This overall virtual absence of gender differences in SOPS/PCP however, is in contrast to a preponderance of reports, which consistently present women as more prone to N than men. Here then is a major difference between SOPS/PCP and N, which, as the original study (Bickersteth, et al, 2018) suggested, represents evidence that SOPS/PCP and N are not identical despite their positive association.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…This overall virtual absence of gender differences in SOPS/PCP however, is in contrast to a preponderance of reports, which consistently present women as more prone to N than men. Here then is a major difference between SOPS/PCP and N, which, as the original study (Bickersteth, et al, 2018) suggested, represents evidence that SOPS/PCP and N are not identical despite their positive association.…”
Section: Discussionmentioning
confidence: 89%
“…The Safety-Oriented Personality Style or Phobicentric Psychopathology Individual Questionnaire (SOPS/PCPIQ). To assess SOPS/PCP attributes the SOPS/PCPIQ (Bickersteth, et al, 2018)were administered. SOPS/PCPIQ consists of 29 items that measure the safety-oriented personality style using a six-point Likert-style scale, with a range from 0 (Never) to 5 (Very often).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations